Valorizing indigenous goat milk: functional, nutritional, and sensory properties of Halloumi cheese from northern Kazakhstan - Kapshakbayeva, Zarina; Utegenova, Assiya; Assirzhanova, Zhanna; Agibaeva, Aliya; Omarova, Karina; Jumazhanova, Madina; Kyrykbayeva, Shynar; Baybalinova, Gulmira; Khaimuldinova, Altyngul; Baikadamova, Assemgul; Zhakupbekova, Shugyla (Frontiers in Sustainable Food Systems, 2025)
IntroductionConsumer interest in functional dairy foods has grown, yet limited data exist on Halloumi cheese produced from indigenous goat milk in Kazakhstan. This study aimed to evaluate the nutritional, functional, and sensory attributes of goat milk Halloumi compared with sheep and cow milk variants.MethodsFresh goat, sheep, and cow milk from northern Kazakhstan was processed into Halloumi cheese under standardized conditions. Nutritional composition, amino acid and fatty acid profiles, antioxidant capacity (DPPH and ABTS assays), microbiological safety, and sensory properties were assessed. Statistical significance was determined using one-way ANOVA with Tukey’s post-hoc test (p < 0.05).Results and discussionGoat milk Halloumi exhibited significantly higher antioxidant activity (DPPH 75.5 ± 1.2%; ABTS 15.8 ± 0.5 mg Trolox/g) than sheep (70.2 ± 1.0%; 13.6 ± 0.4 mg TE/g) and cow variants (62.8 ± 0.8%; 11.9 ± 0.3 mg TE/g). It also contained higher levels of essential amino acids and a favorable fatty acid profile enriched in medium-chain and omega-3 fatty acids. Microbiological testing confirmed safety and elevated lactic acid bacteria counts, while sensory evaluation indicated strong consumer acceptance. The findings demonstrate that indigenous goat milk Halloumi combines superior nutritional composition, antioxidant potential, and sensory quality. Benchmarking against other cheeses further suggests its distinct functional properties, although cross-study differences in assay protocols should be considered.ConclusionGoat milk Halloumi represents a safe, functional dairy product that supports sustainable, resilient, and health-oriented food systems. Its production from indigenous goat milk also highlights the value of regional resources in diversifying dairy products and strengthening local food security.